EOQ Development Model in Optimize Raw Material Inventory - Kartika, I Made; Adi Suwandana, I Made; Bagus Wirya Gupta, I Gusti; Denny Herlambang, Putu Gede (Bright Institute, 2022)
The purpose of this study was to determine the amount of safety inventory, order frequency, minimum inventory, maximum inventory limit, total Melon product inventory costs needed by PT. Rajawali Asia Bali uses the EOQ method. Data analyzed using the EOQ method shows that PT. Rajawali Asia Bali safety stock, it is very necessary to support the smooth distribution process that takes place. In accordance with the calculations with the formula, there is a safety stock that must be provided by PT. Rajawali Asia Bali is equal to 7,201 boxes. Planning for Sweet Corn products at PT. Rajawali Asia Bali using the EOQ method has 48.069 boxes.